The Impacts of Quarry Activities on Eco-Hydrological Systems - Mior Azman, Mohamad Hafizi (Universiti Teknologi PETRONAS, 2017)
Nowadays, the demand for the mineral resources such as limestone is increasing due to the increase of the concrete and other productions. In Malaysia, the mining and quarrying activities contribute a large portion of the nation’s economy. In the other hand, the quarry activities also can bring some negative impacts to flora and fauna and environment of its surrounding area. In this study, the scope of the study is to investigate the impacts of quarry activities on eco-hydrological system in the area in which it has focused on the impacts of the activities on the surface water by analysing it in three main parameters such as hydraulic, hydrology and water quality of the natural surface water. The objectives of the study are to measure and examine the identified parameter which are hydraulic, hydrology and water quality if the stream. Then, the data obtained from the study will be used in the analysis part to propose a detention pond to manage the storm water systems in the study area. By performing this study, it can determine the level of impact of the quarry activities on the eco-hydrological system at the area and can propose a suitable mitigation plan to reduce the impact in the future.